УРОЖАЙНІСТЬ КВАСОЛІ ЗАЛЕЖНО ВІД ІНОКУЛЯЦІЇ НАСІННЯ ТА РЯДКОВОГО ВНЕСЕННЯ ДОБРИВ У СХІДНОМУ ЛІСОСТЕПУ УКРАЇНИ (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Introduction. The plant nutrition system which uses seed inoculation with nitrogen-fixing drugs is a big advance in the technology of growing common beans. The question of the effect of mineral nutrition on symbiotic activity, growth and yield of beans is debatable. Now complex granulated organic-mineral preparations in chelated form enriched with macro- and microelements and organic nitrogen are produced.The purpose of the research was to study the effectiveness of pre-sowing seed inoculation in combination with the introduction of new versions of mineral fertilizers on forming bean yield in the conditions of the Eastern Forest Steppe of Ukraine.Research materials and methods. In 2020-2021, field studies were conducted at the university's experimental field to determine the effect of pre-sowing seed treatment and row fertilization on the yield of beans of the Mavka variety. Field experiments were carried out by the method of split plots in three repetitions. The total area of the site is 12 m², the registered area is 10 m². The norm of bean seed sowing was 500,000 pieces/ha. The scheme of the two-factor experiment is as follows: factor A – pre-sowing seed treatment: 1. H2O (control), 2. Rhizohumin; Factor B – row application of fertilizers: 1. No fertilizers (control), 2. Nitroamophoska (NAFK), 3. Dura SOP Actibion, 4. Dura SOP Phos, 5. Dura SOP Elite, 6. Renovation Fuerza.Research results. It was established that the use of Nitroamofoska (a complex nitrogen fertilizer NH4H2PO4+NH4NO3+KCl) and new formulations of fertilizers, such as Actibion, Phos, Elite and Fuerza, increase the survival of plants before harvesting compared to the absolute control - pre-sowing treatment of seeds with water without row application of fertilizers.The application of fertilizers improved the formation of structural parameters of the bean crop, especially on variants with seed inoculation with Rhizohumin.On average, over the two years of research, the highest yield of beans was obtained on the Elite variants: with pre-sowing treatment of seeds with water - 1.75 t/ha (increase of 0.25 t/ha or 16.7%), with inoculation with Rhizohumin - 1.82 t /ha (increase of 0.32 t/ha or 21.3%). The second highest yield of beans turned out to be the use of Fuerza fertilizer, respectively 1.74 t/ha (increase of 0.24 t/ha or 16.0%) and 1.80 t/ha (increase of 0.30 t/ha or 20.0%). Actibion fertilizer provided a yield of 1.71 t/ha (increase of 0.21 t/ha or 14.0%) with pre-sowing seed treatment with water and 1.75 t/ha (increase of 0.25 t/ha or 16.7%) by seed inoculation with Rhizoguminum.Fos fertilizer was less effective in terms of bean crop formation: with pre-sowing treatment of seeds with water – 1.64 t/ha, with seed inoculation with Rhizohumin – 1.68 t/ha; an increase of 0.14 and 0.16 t/ha or 9.3 and 12.0%, respectively. Row application of Nitroammofoska provided the smallest increase in yield relative to absolute control: with pre-sowing treatment of seeds with water – 0.09 t/ha or 6.0%, with seed inoculation with Rhizohumin – 0.15 t/ha or 10.0%.Conclusions. Row application of new formulations of fertilizers in a comination with pre-sowing treatment of seeds with Rhizogumin ensured a higher yield compared to the application of Nitroamofoska. Among the investigated fertilizers, the highest yield on average over two years of research was obtained on the variants Rhyzohumin + Elite - 1.82 t/ha and Rhyzohumin + Fuerza - 1.80 t/ha; on control - 1.50 t/ha.
Keywords: beans; inoculation; fertilizers; crop structure; yield